Trace Fossils of Dung Beetles - Genise, Jorge Fernando (Ichnoentomology, 2016)
The ichnogenera Coprinisphaera, Quirogaichnus, Eatonichnus, Chubutolithes, Pallichnus, Scaphichnium and other meniscate burrows attributed to dung beetles are reviewed. Coprinisphaera is one of the most emblematic insect trace fossil from paleosols: it is one of the first described, one of the most abundant and recorded, and it is also subject of novel studies detailed along other chapters. The history of research on this ichnogenus is reviewed along with the detailed morphology of its ichnospecies, C. murguiai, C. lazai, C. kitu, C. akatanka, C.tonnii, C.kheprii, C. kraglievichi, C. laetoliensis, C. ndolayana, and C. cotiae, and possible producers. It has been interpreted since its recognition in paleosols as dung beetle brood balls. Quirogaichnus coniunctus is represented by brood balls clustered in a cavity and interpreted as a compound nest of a dung beetle. Eatonichnus utahensis, E. claronensis and a new ichnospecies are ellipsoid chambers surrounded by a helical wall composed of pellets and interpreted as dung beetle pupation chambers. Chubutolithes gaimanensis is interpreted herein as a dung beetle pupation chamber by comparison with extant ones and Eatonichnus. It also shows externally rows of imbricated pellets. Pallichnus dakotensis is a simple trace represented by a spheroidal structure shown a rounded scar at one pole and interpreted as the pupation chamber of Geotrupinae. Scaphichniun hamatum and other meniscate burrows have been interpreted as Geotrupinae cylindrical brood masses. Finally, the chapter reconstructs a possible evolution of coprophagy and necrophagy in Scarabaeidae as reflected by trace fossils. Color plates of type material, morphological details and representative cases are provided.